2011
DOI: 10.1002/eji.201041363
|View full text |Cite
|
Sign up to set email alerts
|

Specific depletion reveals a novel role for neutrophil‐mediated protection in the liver during Listeria monocytogenes infection

Abstract: Summary Previous studies have suggested that neutrophils are required for resistance during infection with multiple pathogenic microorganisms. However, the depleting antibody used in those studies binds to both Ly6G and Ly6C (anti-Gr-1; clone RB6-8C5). This antibody has been shown to not only deplete neutrophils, but also monocytes, and a subset of CD8 T cells. Recently, an antibody against Ly6G has been characterized which specifically depletes neutrophils. In the present study, neutrophils are depleted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
118
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 44 publications
12
118
2
Order By: Relevance
“…Instead, TNF-a secreted from by neutrophils seems to help in killing LM-infected hepatocytes. These results of Carr et al [13] go against previous conclusions drawn regarding the roles of neutrophils in LM infection observed on the basis of anti-Gr-1 mAb-mediated depletion experiments, and reveal a precise role for neutrophils in controlling LM infection in the spleen and liver. Interestingly, Wojtasiak et al have shown in mice that specific depletion of Ly-6G 1 neutrophils does not modulate disease or alter virus replication following intranasal infection with HSV-1, whereas treatment of HSV-1-infected mice with the anti-Gr-1 mAb (clone RB6-8C5) leads to exacerbated virus replication and disease severity and increased mortality [14].…”
contrasting
confidence: 81%
See 3 more Smart Citations
“…Instead, TNF-a secreted from by neutrophils seems to help in killing LM-infected hepatocytes. These results of Carr et al [13] go against previous conclusions drawn regarding the roles of neutrophils in LM infection observed on the basis of anti-Gr-1 mAb-mediated depletion experiments, and reveal a precise role for neutrophils in controlling LM infection in the spleen and liver. Interestingly, Wojtasiak et al have shown in mice that specific depletion of Ly-6G 1 neutrophils does not modulate disease or alter virus replication following intranasal infection with HSV-1, whereas treatment of HSV-1-infected mice with the anti-Gr-1 mAb (clone RB6-8C5) leads to exacerbated virus replication and disease severity and increased mortality [14].…”
contrasting
confidence: 81%
“…Altogether these recently published reports [13][14][15] highlight the importance of the Ly6G mAb (clone 1A8) for investigating the functions of neutrophils. Furthermore, the findings [13][14][15] remind us that all previous studies that used the anti-Gr-1 mAb (clone RB6-8C5) to investigate the roles of neutrophils need to be revisited and their conclusions reconsidered.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…However, activated macrophages display increased resistance to infection by L. monocytogenes (14). Neutrophils have been shown to play an important role in the control of L. monocytogenes infection in vivo (15,16). In vitro, human neutrophils kill a large portion of L. monocytogenes via both oxidative-dependent and -independent processes (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%